Assessment of Energy Efficiency and Energy Poverty of the Residential Building Stock of the City of Seville Using GIS - Antonio J. Aguilar; María L. de la Hoz-Torres; Joaquín Aguilar-Camacho; María Fernanda Guerrero-Rivera (Applied Sciences)
In the European Union, 75% of the residential building stock is estimated to have energy inefficiencies, which increases the probability of falling into energy poverty. Poor thermal conditions reduce the quality of life of dwelling occupants. Renovating the residential building stock is essential to reduce energy consumption, CO2 emissions, and energy poverty in cities. This study aims to assess and map the energy efficiency and energy poverty of residential buildings in Seville at the urban district and census tract level. A total of 45,908 dwellings were evaluated using data from the Energy Performance Certificates database and demographic and economic information from national and official databases. The analysis considers dwelling typology, year of construction, average household income, and geographic location at the district and census tract level. The results show that Seville’s residential building stock performs poorly, with 83% and 92% of dwellings rated “E” or lower for energy consumption and CO2 emissions, respectively. The findings of this GIS-based study help identify urban areas with less efficient buildings and higher energy poverty risk, providing valuable information to develop targeted renovation strategies and reduce the climate impact of Seville’s residential building stock.